Teacher Capacity Building and Effective Teaching and Learning: A Seamless Connection - Egbo, Benedicta (Richtmann Publishing, 2011)
This paper explores the trajectories between teacher capacity building and effective teaching and learning withparticular reference to the Nigerian context where the education system is facing unprecedented challenges. Paradoxically, thesolutions appear to be elusive. This paper argues that as micro-level practitioners, teachers constitute the nexus of anysustainable transformation of the system. To achieve this goal as well as to stem the tide of teacher underperformance, a centralargument in the paper is that building teacher capacity is not only critical to successful teaching and learning, it should also bethe starting point for reconstituting the education system. Towards this end, the paper identifies three context-responsive areasof strategic intervention vis Ã vis teacher capacity building.